Metastable Reprogramming State of Single Transcription Factor-Derived Induced Hepatocyte-Like Cells - Seon In Hwang; Tae Hwan Kwak; Ji Hyun Kang; Jonghun Kim; Hyunseong Lee; Kee-Pyo Kim; Kinarm Ko; Hans R. Schöler; Dong Wook Han (Stem Cells International)
We previously described the generation of induced hepatocyte-like cells (iHeps) using the hepatic transcription factor Hnf1a together with small molecules. These iHeps represent a hepatic state that is more mature compared with iHeps generated with multiple hepatic factors. However, the underlying mechanism of hepatic conversion involving transgene dependence of the established iHeps is largely unknown. Here, we describe the generation of transgene-independent iHeps by inducing the ectopic expression of Hnf1a using both an episomal vector and a doxycycline-inducible lentivirus. In contrast to iHeps with sustained expression of Hnf1a, transgene-independent Hnf1a iHeps lose their typical morphology and in vitro functionality with rapid downregulation of hepatic markers upon withdrawal of small molecules. Taken together, our data indicates that the reprogramming state of single factor Hnf1a-derived iHeps is metastable and that the hepatic identity of these cells could be maintained only by the continuous supply of either small molecules or the master hepatic factor Hnf1a. Our findings emphasize the importance of a factor screening strategy for inducing specific cellular identities with a stable reprogramming state in order to eventually translate direct conversion technology to the clinic.